Bactericidal properties of experimental dental composites based on dimethacrylate resins reinforced by nanoparticles - Lukomska-Szymanska, Monika Magdalena; Kleczewska, Joanna; Bielinski, Dariusz Marian; Jakubowski, Witold; Sokolowski, Jerzy (European Journal of Chemistry, 2014)
The aim of this study was to examine the possibility of replacing a part of the filler in experimental dental composites by nanoparticles with antibacterial potential. Experimental dental composites containing silver nanoparticles deposited on titanium and silica dioxide of different size were analyzed in terms of antibacterial properties. The depth of cure and mechanical properties of composite surface layer were examined. Bactericidal properties were tested according to the LIVE/DEAD cell viability assay. The mechanical properties were determined with a NanoTest 600 instrument. Composites containing silver nanoparticles deposited on titanium dioxide and nanosilica carrier exhibit the strongest antibacterial properties. High content of TiO2 causes strong absorption of light irradiation, which makes their curing process more difficult. Hardness of surface layer increases but the deeper layers of the samples remain uncured. Composites containing nanosilver on titanium dioxide and nanosilica carrier exhibit the highest antibacterial activity. High content of TiO2 causes strong absorption of light irradiation impairing their curing process. The presence of nanosilver changes composite color causing limited light penetration and lower surface hardness.